Cochlear implantees: Analysis of behavioral and objective measures for a clinical population of various age groups. (November 2015) - Greisiger, Ralf; Shallop, Jon K.; Hol, Per Kristian; Elle, Ole Jakob; Jablonski, Greg Eigner
Abstract : Introduction: As of 2014 more than 1200 patients have received a cochlear implant (CI) at Oslo University Hospital (OUS) and approximately half of them have been children. The data obtained from these patients have been used to develop a comprehensive database for a systematic analysis of several objective measurements and programming measurements. During the past 10 years, we have used an objective measurements protocol for our CI surgeries. Our intra-operative protocol includes: Evoked Compound Action Potentials (ECAP), visually observed Electrically evoked Stapedius Reflex Threshold (ESRT), and electrode impedances. Post-operative (Post-OP) programming sessions typically begin 4–6 weeks after surgery and continue on a scheduled basis. The initial programming data include threshold levels (T-levels) and comfortable levels (C-levels) for the different patient age groups. In this study, we compared initial stimulation levels and stimulation levels after at least 1 year of CI with objective measurements obtained intra-operatively. Method: This study focused on the development of a comprehensive database of detailed intra-operative objective measures and post-OP programming measurements from a group of 296 CI patients who received the same type of CI and electrode configuration (Cochlear ® Corporation CI with Contour ® electrode). This group included 92 bilateral CI patients. Measurements from 388 CI devices were studied. Patients were divided into 5 different age groups at the age of implantation: 0–2, 2–5, 5–10, 10–20, and above 20 years in order to investigate age-related differences in programming levels and objective measurements. For the comparison analysis we used T- and C-levels obtained after the last day of initial programming and also after at least 1 year implant use. These programming levels were then correlated with some of the intra-operative objective measurements. Results: T-levels were found to be the lowest for the youngest patient group and increased with age. C-levels varied within age groups and frequency range. Patients above 20 years of age had the highest comfort levels in the low to mid-frequencies (electrodes 22–8) and the lowest comfort levels in the high-frequency range (electrodes 1–7). Correlation coefficients between intra-operative objective measurements and programming levels were found to be in the range of no correlation to moderate correlation. Adult patients had the most significant correlation coefficients between ECAP thresholds and T-levels in the low frequencies. The younger patients aged 10–20 years and 5–10 years had more significant correlations in the higher frequency channels compared to the other age groups. Intra-operative visually observed ESRTs and electrode impedances were not significantly correlated with initial or stable programming levels for the children or adults. Conclusion: Analyzing initial and follow-up mapping levels from previous patients is very important for a CI Center in terms of quality control. The mean T/C-levels reported in this study can provide guidance to our programming audiologists and help them determine the initial programming levels to be stored in the speech processor, especially for very young patients. Unfortunately intra-operative objective measures in our study, such as ECAP, ESRT, and electrode impedances did not provide statistically significant correlations that may help to predict the programming T- and C-levels for all patients. However, we have observed cases where the intra-operative objective measures of ESRT and TECAP profiles were very similar to an individual's MAP profile. It was not possible, however, to determine why some patients did not have an objective measures profile that was similar to their programming levels profile.